Going global: Chinese natural resource policies and their impacts on Latin America - Karin Küblböck; Bernhard Tröster; Christoph Ambach (Austrian Foundation for Development Research (ÖFSE), 2019)
China is today the second-largest economy after the US and the world-leading export nation. The economic and political development of China in the past decades has had a big impact on other parts of the world. The Chinese demand for natural resources has dramatically changed trade volumes and structures in many resource-producing countries. Even though China has recently shifted its internal economic focus away from export manufacturing towards a more consumption and service-based economy, securing the supply of primary commodities remains one of China's main priorities. It is today the world's major consumer of iron ore, steel, coal, zinc, lead, tin, nickel, copper and aluminium. As part of this trend, the relationship between Latin America and the Caribbean (LAC) and China has also intensified over the last two decades. The value of total trade between China and all LAC countries has increased twentyfold since 2000. Taking out Mexico from the LAC dataset reveals that China has become the most important single export market for the remaining LAC countries. Chinese Foreign Direct Investment in LAC has grown significantly since 2000. It has been particularly dynamic from 2010 onwards and is directed primarily towards the raw materials sector. Chinese policy banks have become the largest lender in Latin America in the past two decades, providing more financing to the region than the World Bank and the Inter-American Development Bank (IDB) combined. This paper looks at the role of China in Latin America with a focus on natural resources, and, in particular, minerals. It first describes the evolving economic and diplomatic relations between China and LAC and depicts the main Chinese actors in this region, before giving an overview of developments in the areas of trade, finance and investments. It concludes that if the relationship with China is to contribute to inclusive development in LAC, the countries in the region have to coordinate their efforts in order to obtain greater benefits from the new economic relations.
Keywords: 330; China; Latin America; Trade; Finance; Foreign Direct Investment; Mining